Correction: Khalid et al. Real-Time Plant Health Detection Using Deep Convolutional Neural Networks. Agriculture 2023, 13, 510 - Mahnoor Khalid; Muhammad Shahzad Sarfraz; Uzair Iqbal; Muhammad Umar Aftab; Gniewko Niedbała; Hafiz Tayyab Rauf (Agriculture)
Affiliation Revision [...]